Analisis Tata Letak Fasilitas Kerja Pada Proses Pembuatan Rumah Boneka Dengan Pekerja Penyandang Disabilitas - Surya Perdana; Tiara Tiara; Galuh Krisna Dewanti; Syafa’atun Syafa’atun (Operations Excellence: Journal of Applied Industrial Engineering, 2019)
The layout of the factory is the main foundation in the industrial world, in this study there are problems in the production process of doll houses where most of the workers are persons with disabilities. At the production station, there is a long distance between the material work station, which results in an increase in transfer costs and the amount of production output produced. The method used in this study is a flow diagram and map of the operation process. This method is used to determine the flow of the production process from the beginning of the raw material to the process of checking the finished product. This study uses ARC to be able to find out the relationship of each work station and find out the reasons for each work station. The flow of the production process of doll houses in the company still needs to be improved. Because between a work station and other work stations it is not regular according to the flow of the production process. Based on the results of research on dollhouse production it was found that the amount of transportation between each work station and warehouse resulted in wasteful production time. It was concluded that there is a critical path, namely the path of the Raw warehouse to the cuttting machine. There is a flow that is too long/far, namely cutting machine to Pattern, pattern path to Jigsaw 1, and the Jigsaw path to Forging.